Seminar by International Board for Plant Genetic Resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
A seminar which was sponsored by CTA on Safeguarding the genetic basis of Africa's traditional crops and organized by the International Board for Plant Genetic Resources (IBPGR) in collaboration with the Kenyan Agricultural Research Institute (KARI)...